eDNA metabarcoding vs metagenomics: an assessment of dietary competition in two estuarine pipefishes - Serite, Conny P.; Emami-Khoyi, Arsalan; Ntshudisane, Ofentse K.; James, Nicola C.; Jansen van Vuuren, Bettine; Bodill, Taryn; Cowley, Paul D.; Whitfield, Alan K.; Teske, Peter R. (Frontiers in Marine Science, 2023)
Understanding the dietary preferences of endangered species can be useful in implementing conservation strategies, including habitat restoration, translocation, and captive breeding. Environmental DNA (eDNA) from feces provides a non-invasive method for analysing animal diets. Currently, metabarcoding, a PCR-based approach, is the method of choice for analysing such data. However, this method has limitations, specifically PCR bias, which can result in the overestimation of the importance of certain taxa and failure to detect other taxa because they do not amplify. The present study compared metabarcoding with metagenomics, a PCR-free method, to assess the diversity of prey items in the feces of a critically endangered South African estuarine pipefish, Syngnathus watermeyeri, and its widely distributed congener S. temminckii to investigate potential dietary competition. The metabarcoding results showed a distinct difference between the diets of S. watermeyeri and S. temminckii, with the former mainly consuming calanoid copepods and the latter preferring caridean shrimp. In each case, a single species dominated the sequences generated by metabarcoding. Metagenomics produced more species identifications, and although the same trend was found regarding the preference of S. watermeyeri for copepods and that of S. temminckii for shrimp, this approach identified additional, albeit yet unidentified, copepod species as being important in the diet of S. watermeyeri. We conclude that the lower number of species identified using metabarcoding was most likely a result of amplification bias, resulting in key copepod species missing from the dietary analysis. These findings suggest that metagenomics is not only a useful complementary method for molecular dietary analysis, but may in some cases outperform metabarcoding. However, metagenomics is even more strongly affected by the lack of reference sequences than is metabarcoding, as the majority of sequences originate from genomic regions that have not yet been sequenced for the putative prey species in question.